Construction Workers Perceptions Toward Safety Culture - Andi Andi (Civil Engineering Dimension, 2008)
Efforts to reduce construction accidents can be initiated by building good safety culture. Researches concerning safety culture, however, are still limited. This research aims to empirically gauge workerâs perception toward safety culture in construction projects. Data were obtained through questionnaire survey to three large construction projects in Surabaya. Two hundreds and seven sets of questionnaires were gathered and used for subsequent analyses. Results show that in general workersâ perception toward safety culture are quite good. Further analysis indicates that workers in the three projects have different safety culture perceptions, especially on factors of top management commitment, safety rules and procedures, communication, and workerâs competency.